A CARACTERIZAÇÃO POLÍTICO-PEDAGÓGICA DA BNCC: A POLÍTICA CURRICULAR NO CONTEXTO DA FORMAÇÃO PARA O CAPITAL - FLAVIA MOREIRA RIBEIRO (2021)
This research analyzes the political-pedagogical characterization of the Common National Curriculum Base (BNCC) implemented as Brazilian public policy, expressed in the context of capital formation, through the neoliberal configuration of the State. The study aims to understand the political-pedagogical impact of the State as a mediation of the hegemonic rationality of capital, in the context of the historical affirmation of the urban-industrial model of the beginning of the 20th century and its constant effort to restructure. Thus, the research starts from the recognition of the BNCC curriculum policy as a strategy of the neoliberal State as a functional pedagogical discipline of education to the needs of productive reorganization and reproduction of economic demands worldwide. With a qualitative approach, the research is methodologically structured, as a theoretical exercise, based on the Dialectical Historical Materialism method, as an exercise in interpreting reality and understanding social facts. The analysis is guided by the theoretical contribution of the Italian philosopher Antônio Gramsci (1968), among other researchers who are dedicated to understanding the influence of production methods on educational intentions, such as Ramos (2002), Silva (2008), Frigotto (2013), Antunes and Pinto (2017).The work concludes with the recognition of the BNCC as a curricular policy positioned within the scope of curricular reformism, underway in Brazil from the 1990s, as an instrument of the neoliberal agenda for the repositioning of the state apparatus, also of the school, in view of its repositioning and conservation requirements hegemonic. This repositioning is, politically and pedagogically, deeply characterized by the centrality of the organization of the education system by matrices of competences and skills and by the direct impact on the curricula of institutions and educational networks; on the reference matrices of assessments and exams; on teacher training policy; and about the teaching material.